Distinct cerebral cortical perfusion patterns in idiopathic normal‐pressure hydrocephalus - Kang, Kyunghun; Jeong, Shin Young; Park, Ki‐Su; Hahm, Myong Hun; Kim, Jaeil; Lee, Ho‐Won; Kim, Chi‐Hun; Yun, Eunkyeong; Han, Jaehwan; Yoon, Uicheul; Lee, Sang‐Woo (Human brain mapping, 2023)
The aims of the study are to evaluate idiopathic normal‐pressure hydrocephalus (INPH)‐related cerebral blood flow (CBF) abnormalities and to investigate their relation to cortical thickness in INPH patients. We investigated cortical CBF utilizing surface‐based early‐phase 18F‐florbetaben (E‐FBB) PET analysis in two groups: INPH patients and healthy controls. All 39 INPH patients and 20 healthy controls were imaged with MRI, including three‐dimensional volumetric images, for automated surface‐based cortical thickness analysis across the entire brain. A subgroup with 37 participants (22 INPH patients and 15 healthy controls) that also underwent 18F‐fluorodeoxyglucose (FDG) PET imaging was further analyzed. Compared with age‐ and gender‐matched healthy controls, INPH patients showed statistically significant hyperperfusion in the high convexity of the frontal and parietal cortical regions. Importantly, within the INPH group, increased perfusion correlated with cortical thickening in these regions. Additionally, significant hypoperfusion mainly in the ventrolateral frontal cortex, supramarginal gyrus, and temporal cortical regions was observed in the INPH group relative to the control group. However, this hypoperfusion was not associated with cortical thinning. A subgroup analysis of participants that also underwent FDG PET imaging showed that increased (or decreased) cerebral perfusion was associated with increased (or decreased) glucose metabolism in INPH. A distinctive regional relationship between cerebral cortical perfusion and cortical thickness was shown in INPH patients. Our findings suggest distinct pathophysiologic mechanisms of hyperperfusion and hypoperfusion in INPH patients. The present study investigates cerebral blood flow (CBF) and cortical thickness using surface‐based analysis of early‐phase 18F‐florbetaben PET and MRI in patients with idiopathic normal‐pressure hydrocephalus (INPH). INPH patients had significantly increased CBF with a concomitant increase in cortical thickness in areas located in the high convexity of the frontal and parietal cortical regions, and significantly decreased CBF without a concomitant change in cortical thickness in the ventrolateral frontal cortex, supramarginal gyrus, and temporal cortical regions in comparison to control subjects. Our findings suggest distinct pathophysiologic mechanisms of hyperperfusion and hypoperfusion in INPH patients.